NM23-H1 Expression of Head and Neck Squamous Cell Carcinoma in Association With the Response to Irradiation - Wang, Yi-Fen; Lin, Yi-Ke; Lin, Chin-Ping; Chen, Yu-Jen; Chang, Chun-Ju (Frontiers in Oncology, 2021)
A low NM23-H1 expression in head and neck squamous cell carcinoma (HNSCC) was found to be associated with poor clinical outcome. Therefore, we investigated the role of NM23-H1 in the susceptibility of HNSCC cells to irradiation and its clinical significance. An in vitro study was also conducted to validate the results. Furthermore, we used immunohistochemistry to analyze NM23-H1 expression found in specimens of 50 HNSCC patients with cervical metastases receiving postoperative radiotherapy. Low tumor NM23-H1 expression was associated with locoregional recurrence of HNSCC (p=0.040; Hazard ratio=5.62) and poor clinical outcome (p=0.001; Hazard ratio=4.90). To confirm the effect of NM23-H1 on radiation-induced cytotoxicity, we generated several stable clones derived from a human HNSCC cell line (SAS) using knockdown and overexpression of NM23-H1. Knockdown of NM23-H1 decreased the radio-sensitivity of SAS cells, possibly associated with a decrease in the radiation-induced G2/M-phase accumulation and upregulation of cyclin B1. On the contrary, overexpression of NM23-H1 can reverse the aforementioned adverse results. Consequently, we suggest that NM23-H1 expression may be considered as a potential therapeutic treatment option for HNSCC patients.